â€œWebsites Are More Helpful Because I Can Comebackâ€: Studentsâ€™ Perspective on the Use of Learning Websites - Syahputri, Veni Nella; Rahma, Endah Anisa; Setiyana, Rusma (International Conference on Multidisciplinary Research, 2021)
During the COVID-19 pandemic, the educational system has changed. This brought a significant shift to class and teaching management as well. Teachers manage their classes in various ways by utilizing digital platforms. This study aims at finding out students’ perspective on using website in the teaching and learning process. This study was conducted by using qualitative approach design, with the descriptive case study method. There were 17 university students at Universitas Teuku Umar who were involved as the respondents in this study. In data collection, an interview set consisting of 6 questions was distributed to students. Later, the data were analyzed using interactive analysis through the three steps, which are data identification, data display, and data verification. The result shows that students have positive feedbacks toward the use of websites during online learning rather than other digital platforms. The reasons are the constant availability, length adequacy, and completeness. The implication of this study is that it is more preferrable for students to learn by using websites—or better known as e-learning system—rather than other platforms. Keywords: learning websites, e-learning, positive feedback, digital classroom, COVID-19 pandemic.